2017
DOI: 10.1152/advan.00177.2016
|View full text |Cite
|
Sign up to set email alerts
|

The renal and cardiovascular effects of natriuretic peptides

Abstract: The landmark report by de Bold et al. in 1981 signified the heart as one of the endocrine organs involved in fluid and salt balance (de Bold AJ, Borenstein HB, Veress AT, Sonnenberg H. 28: 89-94, 1981). Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) are secreted from cardiomyocytes in response to cardiac stretch as in the case of heart failure, whereas C-type natriuretic peptide (CNP) is secreted from endothelial and renal cells in response to cytokines and endothelium-dependent agonists,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 59 publications
0
74
0
Order By: Relevance
“…It is possible that the significant increase in PAP during incremental exercise causes secretion of natriuretic peptides by cardiomyocytes in response to cardiac stretch (Wong et al. ), and thus pGC activation. In support of this hypothesis, PAP and the pulmonary vasodilator effect of PDE5 inhibition were highly correlated ( r 2 = 0.82; P < 0.05; Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the significant increase in PAP during incremental exercise causes secretion of natriuretic peptides by cardiomyocytes in response to cardiac stretch (Wong et al. ), and thus pGC activation. In support of this hypothesis, PAP and the pulmonary vasodilator effect of PDE5 inhibition were highly correlated ( r 2 = 0.82; P < 0.05; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of pGC can be stimulated by natriuretic peptides (ANP and BNP) (Kobialka and Gorczyca 2000). It is The Physiological Society and the American Physiological Society possible that the significant increase in PAP during incremental exercise causes secretion of natriuretic peptides by cardiomyocytes in response to cardiac stretch (Wong et al 2017), and thus pGC activation. In support of this hypothesis, PAP and the pulmonary vasodilator effect of PDE5 inhibition were highly correlated (r 2 = 0.82; P < 0.05; Fig.…”
Section: The No-cgmp Pathway In Neonatal Pulmonary Vascular Disease Dmentioning
confidence: 99%
“…Many studies have shown that HIV/AIDS has a significant effect on health and that good indicators include mortality rates and life expectancy. For example, two studies in the field of global inequality of life expectancy have shown that the 6 years of the difference in life expectancy between Africa and North America is related to AIDS (Dorling D;Wong et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Education is an important component of HDI and it is necessary to include that parameter, especially in countries with low-and medium-income. In most African countries, HIV/AIDS has shown an inverse association with primary education, especially in girls (Wong et al, 2017). In these countries the death of parents due to AIDS is frequent; the issue of family economic situations will aggravate and also will increase the number of children dismissed from school (Boulogne et al, 2017;Lou et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, new era in use of NPs in monitoring of HF evolution has been opened after implementation in the routine clinical practice (Malek and Gaikwad, 2017). Recent clinical trials have been shown that nephrilisin inhibition auxiliary to chronic renin-angiotensin system blockage with LCZ696 (Sacubitril/Valsartan) may increase the bioavailability of NPs and promotes additional benefits the cardio-renal system and hence protected against all-cause mortality, CV mortality and HF death (Wong et al, 2017). Because of biologically active BNP is degraded by neprilysin, in HF patients treated with ARNI circulating level of BNP sufficiently increases, whereas NT-proBNP concentration declines dramatically.…”
Section: Biomarker(s)-based Strategies Of Pharmacological and Non-phamentioning
confidence: 99%